The Linguistic Construction of Confirmation Niches in Online Comment Sequences (Altre Modernità, 2018)
This paper analyses the dialogic structure occurring in an asynchronous discussion forum taken as a talk-in-interaction venue, and a confirmation niche.I employ a conversation-analysis based approach adapted to online written texts (Antaki et al. 2005; Herring, 2013; Giles et al. 2015) and studied in the context of forum participative writings (Stommel and Lamerichs, 2014) as an interactional event (Herring 2007), and confirmation site (Quattrociocchi and Vicini, 2016).Results show that the exchange is construed by adapting conversation-like concepts within an asynchronous and written mode of communication, and that the participatory framework is the ground where opposing groups interact and build a personal confirmation niche, which represents a relevant barrier to a critical discourse attitude.-